Temperature Anisotropy Instabilities Stimulated by the Solar Wind Suprathermal Populations - Lopez-Escobar, R (Frontiers Media S.A., 2022)
This review paper compiles recent results obtained by the present group of authors describing the effects of suprathermal populations present in space plasmas (up to a few keVs) on temperature anisotropy instabilities. Of particular interest are the electromagnetic cyclotron and firehose excitations, which play a major role in limiting temperature anisotropy, resulting, for instance, from the adiabatic expansion of the solar wind. Relying on a rigorous modeling and interpretation of the observed velocity distributions, both theoretical models and numerical simulations indicate a systematic stimulation of these excitations in the presence of suprathermal populations of electrons or protons. Moreover, the enhanced fluctuations react back on particles, and determine a faster and deeper relaxation of their anisotropy. The present comparative analysis suggests that previous studies, considering only quasi-thermal low-energy populations, may have significantly underestimated these excitations and their implications in various applications in space plasmas. Copyright © 2022 Lazar, López, Shaaban, Poedts, Yoon and Fichtner.